Grain sorghum response to water supply and environment - Broeckelman, Jonathan (Kansas State University, 2016)
Sorghum [Sorghum bicolor (L.) Moench] has greater drought resilience than many other crops, producing food in the most stressful environments. Sorghum is a reasonable crop choice for farmers working with limited-water supply. The objective of this study was to compare sorghum hybrids differing in yield strategies under varying water supply environments. Yield, biomass, grain harvest index (HI), and yield components (seed number and seed weight) were compared in both rainfed and irrigated situations. Field experiments were established in 2014 and 2015 at Topeka, Scandia, Hutchinson, Garden City, and Tribune, KS. Three sorghum hybrids (Pioneer 85Y40, Pioneer 84G62, and Dekalb 53-67) with different yield potentials at varying water supply were studied. Hybrids 85Y40 and 84G62 tended to have greater yields than hybrid 53-67 when the environment's average yield level was greater than 8.5 Mg haˉ¹. The opposite scenario where hybrid 53-67 had greater yields than the other two hybrids tended to occur for environments yielding less than 8.5 Mg haˉ¹. Both biomass and HI were significantly correlated with grain yield (r values of 0.62 and 0.32 respectively), with biomass having an overall stronger correlation than HI in all environments. In yield group 3 (<8.5 Mg haˉ¹), biomass was much more strongly correlated (r=0.85) to yield than in the yield groups 1 and 2 (>9.5 Mg haˉ¹ and 8.5-9.5 Mg haˉ¹ with r values of 0.35 and 0.52 respectively) suggesting that biomass production is of utmost importance for yield production in drought prone environments. Harvest index on the other hand had a much stronger correlation with yield in group 1 (r=0.62) when compared to group 2 and 3 (r 0.13 and 0.36 respectively) showing the importance of not only biomass, but also of HI to maximize yield in high yielding environments. Hybrids 85Y40 and 84G62 had larger HI values relating to the yield trends in the highest yielding environments. Seed number had a stronger correlation with yield (r=0.77) than seed weight (r=0.37) supporting the importance of increasing seed number to improve yield in sorghum.
Keywords: Sorghum; Response; Environment; Yield components